2020
DOI: 10.1371/journal.pone.0241464
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety as a mediator of relationships between perceptions of the threat of COVID-19 and coping behaviors during the onset of the pandemic in Poland

Abstract: At the beginning of the COVID-19 pandemic (10–14 March, 2020) we conducted a survey (n = 1028) of a nationally representative sample (age, sex, and locale) in Poland. Respondents indicated how strong they thought the threat was to themselves, to Poland, and the world. They also described their emotional reactions to the pandemic, which we used to calculate three scores: Anxiety , Hopelessness , and Panic . Respondents also indicated how often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
(43 reference statements)
6
36
0
2
Order By: Relevance
“…The predictor variables included in our models were selected in light of the theoretical account of over-purchasing that we outlined in our introduction. However many were also consistent with previous speculation about the psychological factors involved in this phenomenon, such as personality and anxiety towards COVID-19 [12,74,75], but some had never before been considered in this context, for example death anxiety and analytical reasoning.…”
Section: Discussionsupporting
confidence: 87%
“…The predictor variables included in our models were selected in light of the theoretical account of over-purchasing that we outlined in our introduction. However many were also consistent with previous speculation about the psychological factors involved in this phenomenon, such as personality and anxiety towards COVID-19 [12,74,75], but some had never before been considered in this context, for example death anxiety and analytical reasoning.…”
Section: Discussionsupporting
confidence: 87%
“…Sorokowski et al (2020) showed that mere exposure to information about COVID-19 was associated with higher anxiety levels. In a Polish study, it has been documented that the levels of perceived threat, anxiety, and hopelessness did significantly increase right after the first fatalities were reported (Cyprya nska & Nezlek, 2020). A survey conducted in March 2020 showed that nearly half of American people felt anxious about the coronavirus, becoming seriously ill, or about their relatives getting COVID-19 (American Psychiatric Association, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we hypothesized that the threat-emotion-coping sequence proposed by Lazarus and Folkman might be more robust at the beginning of the pandemic. At this time, the threat and impact of COVID-19 on people's lives were greater, leading people to experience more emotional distress, and therefore, develop coping mechanisms [39]; in this case, eating more comfort food. Accordingly, we expect that this mediation effect decreased over time, due to chronic exposure to the pandemic and the development of emotion regulation processes [34].…”
Section: Introductionmentioning
confidence: 99%